COMPARATIVE CHARACTERISTICS OF DENTAL CARIES AND ITS COMPLICATIONS IN CHILDREN OF POLTAVA REGION - A.I. Maksymenko; A.S. Mosiienko; O.V. Sheshukova; I.O. Kuz; T.V. Polishchuk; K.S. Kazakova (Український стоматологічний альманах, 2023)
Despite the high level of development of dental technologies, caries, and its complications occupy a leading place in the structure of dental pathology in children nowadays. This is a difficult social, scientific, and practical problem, which determines the relevance of this research.